The potential role of Wolbachia in controlling the transmission of emerging human arboviral infections. Issue 1 (February 2017) - Kamtchum-Tatuene, Joseph; Makepeace, Benjamin L.; Benjamin, Laura; Baylis, Matthew; Solomon, Tom
Abstract : Purpose of review: Wolbachia is a genus of Gram-negative intracellular bacteria that is naturally found in more than half of all arthropod species. These bacteria cannot only reduce the fitness and the reproductive capacities of arthropod vectors, but also increase their resistance to arthropod-borne viruses (arboviruses). This article reviews the evidence supporting a Wolbachia -based strategy for controlling the transmission of dengue and other arboviral infections. Recent findings: Studies conducted 1 year after the field release of Wolbachia -infected mosquitoes in Australia have demonstrated the suppression of dengue virus (DENV) replication in and dissemination by mosquitoes. Recent mathematical models show that this strategy could reduce the transmission of DENV by 70%. Consequently, the WHO is encouraging countries to boost the development and implementation of Wolbachia -based prevention strategies against other arboviral infections. However, the evidence regarding the efficacy of Wolbachia to prevent the transmission of other arboviral infections is still limited to an experimental framework with conflicting results in some cases. There is a need to demonstrate the efficacy of such strategies in the field under various climatic conditions, to select the Wolbachia strain that has the best pathogen interference/spread trade-off, and to continue to build community acceptance. Summary: Wolbachia represents a promising tool for controlling the transmission of arboviral infections that needs to be developed further. Long-term environmental monitoring will be necessary for timely detection of potential changes in Wolbachia /vector/virus interactions.